2022
DOI: 10.3390/polym14061140
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Dielectric Properties of Fly Ash Geopolymer/Sugarcane Bagasse Ash Composites

Abstract: Fly ash (FA) and sugarcane bagasse ash (SCBA) are the wastes from lignite power plants and sugar industries, usually disposed of as landfills. In this research, these wastes were effectively utilized as a construction material, namely geopolymer. The effect of the SCBA (0–40 wt.%) addition to the FA geopolymers was investigated. The compressive strength of the FA geopolymers was reduced with the SCBA addition. The reduction was mainly due to the presence of the highly stable and non-reactive quartz (SiO2) phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…It can be observed that the dielectric constant for all samples decreases with increasing frequency. These findings corroborate the works of Chuewangkam et al 32 and Hanjitsuwan et al 33 , which could be attributed to the highly porous microstructure characteristics of the geopolymer composites. In general, there are no significant differences between the permeability of the synthesized geopolymer composites indicating that BiNP did not alter the charge localization.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It can be observed that the dielectric constant for all samples decreases with increasing frequency. These findings corroborate the works of Chuewangkam et al 32 and Hanjitsuwan et al 33 , which could be attributed to the highly porous microstructure characteristics of the geopolymer composites. In general, there are no significant differences between the permeability of the synthesized geopolymer composites indicating that BiNP did not alter the charge localization.…”
Section: Resultssupporting
confidence: 92%
“…At low frequencies, the dielectric response is due to the interfacial polarization of the composite material. The molecules obtained sufficient time at this frequency to rotate and change orientation towards the applied alternating current 32 . However, high frequency causes relaxation of the polarization process due to the insufficient time for re-orientation, thereby decreasing the Ɛ r 34 .…”
Section: Resultsmentioning
confidence: 90%
“…Sugarcane bagasse is used as fuel instead of diesel for steam boilers to generate the energy needed to run machinery and industrial processes. To obtain the required steam, the sugarcane bagasse is burned in a boiler at temperatures up to 600 • C. On the basis of past research, the raw sugarcane bagasse ash was sieved with a 75 µm sieve to remove undesired brittle particles, such as incompletely burned sugarcane bagasse, and to enhance pozzolanic reactivity [21,23,33]. Only those particles getting passed through the 75 µm size were picked up and used as raw sugarcane bagasse ash (RSCBA) in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Fly-ash peaks were also observed. It consisted of quartz (Q), Anhydrite (A) (CaSO₄), hematite (F) (Fe₂O₃), and calcium oxide (C) (CaO) [7].…”
Section: The Effect Of Grinding Hoursmentioning
confidence: 99%